(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
According to WHO, allergic diseases account for 35 to 40 percent of the world’s population, and the incidence rate varies greatly from country to country. The XXI century, according to the conclusion of this organization, is the century of allergic diseases. The formation and spread of allergic diseases in the world is due to the influence of environmental factors, the appearance of new allergens, violation of microecology (intestinal flora, skin, mucous membranes), stress, excessive use of medicines. This article discusses the types of allergic diseases, clinical course, treatment methods, preventive measures.